Low-temperature strategy toward Ni-NC@Ni core-shell nanostructure with Single-Ni sites for efficient CO2 electroreduction. (November 2020) - He, Yu; Li, Yunxiang; Zhang, Jinfeng; Wang, Shengyao; Huang, Dekang; Yang, Gaoliang; Yi, Xinli; Lin, Huiwen; Han, Xiaopeng; Hu, Wenbin; Deng, Yida; Ye, Jinhua
Abstract: Single-atom incorporated carbon materials are of great significance for diverse electrochemical applications. However, issues of high pyrolysis temperature and high energy dissipation in the synthesis, as well as the insufficient exposure of the active sites, remain to be resolved. Here we develop a low-temperature (as low as 450 °C) chemical vapor deposition strategy to prepare a sheet-like open nanostructure with Ni nanoparticle wrapped by Ni–N species dispersed carbon layer (Ni-NC@Ni). Such a Ni-NC@Ni catalyst exhibits a remarkable CO2 electroreduction performance, including the high selectivity for CO product (Faradaic efficiency 87%) and a high current density of 14.8 mA cm −2 at a moderate overpotential of 670 mV, as well as the long-term stability over 150 h. The experimental analysis confirmed the Ni–N species as the active center and indicated that the open hierarchical nanostructure not only promotes the mass-transfer process but also provides the faster charge transfer channel for efficient CO2 electroreduction. This work paves a new way to develop the single-atom incorporated carbon materials and promotes their application in energy conversion and storage technology. Graphical abstract: Image 1 Highlights: The synthetic temperature of carbon-based SACs was decreased to 450 °C, in contrast to the widely required pyrolysis temperature of 900 °C. Ni-NC@Ni possesses a sheet-like open nanostructure, which ensures effective mass-transport and full exposure of active sites. The metallic Ni nanoparticle core as a good conductor facilitates the charge transfer. High-density isolated Ni–N species ( 4.23 at%) can be obtained in the carbon shell. The cooperative robust single-Ni sites and favorable nanostructure can afford a superior CO2 electroreduction activity.